2021
DOI: 10.1136/bmjopen-2021-051066
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in Delphi surveys to develop core outcome sets: systematic review

Abstract: ObjectivesTo describe the design and conduct of core outcome set (COS) studies that have included patients as participants, exploring how study characteristics might impact their response rates.DesignSystematic review of COS studies published between 2015 and 2019 that included more than one patient, carer or representative as participants (hereafter referred to as patients for brevity) in scoring outcomes in a Delphi.ResultsThere were variations in the design and conduct of COS studies that included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Other Delphi studies with the expert‐by‐experience methodology have demonstrated wide variation in participant dropout, with attrition rates of 16%, 43 22% 46 and 34% 42 . A systematic review of Delphi studies observed a higher level of round two responses when panellists were recruited through treatment centres 56 . As participants for the present study were recruited through ADHD Ireland and social media, attrition could have possibly been reduced by advertising the research in clinical settings.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Other Delphi studies with the expert‐by‐experience methodology have demonstrated wide variation in participant dropout, with attrition rates of 16%, 43 22% 46 and 34% 42 . A systematic review of Delphi studies observed a higher level of round two responses when panellists were recruited through treatment centres 56 . As participants for the present study were recruited through ADHD Ireland and social media, attrition could have possibly been reduced by advertising the research in clinical settings.…”
Section: Discussionmentioning
confidence: 64%
“… 42 A systematic review of Delphi studies observed a higher level of round two responses when panellists were recruited through treatment centres. 56 As participants for the present study were recruited through ADHD Ireland and social media, attrition could have possibly been reduced by advertising the research in clinical settings. However, the research was conducted during Autumn 2020, during COVID‐19 lockdowns in Ireland, and it likely would not have been possible to recruit in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring ongoing parent, patient or public participation in Delphi surveys is well recognised to be challenging. 17 Attrition rates are lower if patient recruitment is through treatment centres rather than patient charities and advocacy organisations 18 ; however, in previous neonatal priority setting work, 7 neonatal unit-based recruitment of parents was also challenging, 8 hence was not pursued during this study. We recognise that the lower levels of participation from parents and former patients may have influenced our final results, but a clear bimodal distribution of rankings with significant clustering of the same topranked and lower-ranked questions was consistent across all stakeholder groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although Delphi studies might simultaneously include different types of stakeholders to answer a common research question, such as health professionals, researchers, caregivers, and patients (Barrington et al, 2021), we used separate groups of BC patients and health professionals to answer two different research questions, to avoid the frequent under-representation of patients in these combined groups (Barrington et al, 2021) and following the methodology of previous Delphi studies carried out (Torres-Castaño et al, 2021). To promote person-centred care, it is opportune to identify the disease-related information needs from the specific patients' perspectives and experiences (Ellis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%